INCIDENCE AND RELATIVE ABUNDANCE OF LACTIC ACID BACTERIA IN RAW MILK OF BUFFALO, COW AND SHEEP - T. Aziz; H. Khan; S.M. Bakhtair; M. Naurin (Journal of Animal and Plant Sciences, 2009)
The study was intended to isolate lactic acid bacteria with promising potential for technological exploitation in dairy products application, and to determine their incidence and relative abundance in raw milk samples of buffalo, cow and sheep origin. In all, 79 identifiable isolates were obtained from 120 samples (40 from each species), thus the overall incidence of lactic bacteria in milk was 66 percent. On the basis of various morphological characteristics the isolates were differentiated into six groups; each group with common and differential characteristics of physiological / biochemical nature was finally identified up to species level. Percent incidence of lactic isolates was highest in cow milk (30/40 = 75%), followed by buffalo milk (27/40 = 68%) and sheep (22/40 = 55%). It was found that buffalo milk contained 5 species viz., Lactobacillus acidophilus (25%), Lactobacillus delbrueckii ssp. bulgaricus (21%), Lactococcus lactis ssp. cremoris (21%), Lactococcus lactis ssp. lactis (19%), and Streptococcus thermophilus (14%). Four species identified in cow milk samples were, Streptococcus thermophilus (34%), Lactococcus lactis ssp. lactis (28%), Lactobacillus delbrueckii ssp. bulgaricus (28%) and Lactococcus lactis ssp. cremoris (10%). Isolates of sheep milk were identified as Lactococcus lactis ssp. lactis (36%), Lactococcus lactis ssp. cremoris (32%), Lactobacillus acidophilus (22%) and Leuconostoc spp. (10%). Only two species, Lactococcus lactis ssp. lactis and Lactococcus lactis ssp. cremoris were found common in all the three types of milk whereas Leuconostoc spp. was unique to sheep milk only.
Keywords: lactic acid bacteria; raw milk; buffalo; cow; sheep